PENGARUH EKSPOR TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Shalomita Agustina; Astri Astuti; Annisa Cahya Kusumawati; Siti Maulidur Rohma; Nur Aini; Dian Oktaviani; Muhammad Ivan Noor Salim; Fhadia Nur Baiti; Riendza Wibowo; Alya Nabila; Nurma Tambunan (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
In a country, the economic component largely determines the survival and progress of the country. This study aims to determine the effect of exports on Indonesia's economic growth. This research uses a descriptive method, namely investigating the circumstances, conditions, or other things that have been mentioned, the results of which are presented in the form of research reports. The initial stage before conducting further analysis requires testing the stationariness of the data. Economic developments in Indonesia's export sector in the 2018-2021 period decreased in December 2018 which reached US$ 14.18 billion or a decrease of 4.89 percent compared to exports in November 2018. This research is expected to be a consideration for the government or authorities to take appropriate steps for the progress of the Indonesian economy.